Application of Biopesticide with Active Ingredients Containing Trichoderma sp., Streptomyces sp., and Chitosan for Groundnut Aphid (Aphis craccivora Koch.) - Mochamad Bima Erdiansyah; Penta Suryaminarsih; Dita Megasari (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Indonesia is the second largest exporter of peanuts to Europe. One of the export requirements is that exported peanuts do not contain pests and high levels of pesticides. Aphis craccivora Koch. is the main pest in peanuts and controlled generally using pesticides which cause high pesticide levels. The aim of this research is to determine the application technique for biopesticide containing enthomopathogen (Streptomyces sp. and Trichoderma sp.) and chitosan which were expected to control the population of the pest Aphis craccivora and the intensity of plant damage. The research was conducted and designed using factorial completely randomized design where the first factor was application time (before and after pest investment). The second factor was chitosan concentration of 0.6%, 0.9%, and 1.2% in potato-sugar extract solution. Each treatment combination was repeated 4 times. The results obtained that the pre-investment application technique with a chitosan concentration of 1.2% was more capable of incrasing the mortality of the pest A. craccivora by up to 70% and the application of biopesticide before investment with a concentration of 1.2% had a lower level of damage, namely 38.25%.